Plasma Exosomes From HLA-Sensitized Kidney Transplant Recipients Contain mRNA Transcripts Which Predict Development of Antibody-Mediated Rejection. Issue 10 (October 2017) - Zhang, Hao; Huang, Edmund; Kahwaji, Joseph; Nast, Cynthia C.; Li, Ping; Mirocha, James; Thomas, David L.; Ge, Shili; Vo, Ashley A.; Jordan, Stanley C.; Toyoda, Mieko
Abstract : Background: Sensitization to HLA remains a significant immunologic barrier to successful transplantation. Identifying immune mechanisms responsible for antibody-mediated rejection (AMR) is an important goal. Here, we explored the possibility of predicting the risk for AMR by measuring mRNA transcripts of AMR-associated genes in plasma exosomes from kidney transplant patients. Methods: Total RNA was extracted from exosomes purified from 152 ethylenediaminetetraacetic acid-plasma samples of 64 patients (18 AMR, 8 cell-mediated rejection [CMR], 38 no rejection in desensitized [DES] and non-DES control groups) for reverse transcription into cDNA, preamplification and then real time quantitative polymerase chain reaction (qPCR) for 21 candidate genes. The mRNA transcript levels of each gene were calculated. Comparisons were made among 4 patient groups for each gene and also for a gene combination score based on selected genes. Results: Among 21 candidate genes, we identified multiple genes (gp130, CCL4, TNFα, SH2D1B, CAV1, atypical chemokine receptor 1 [duffy blood group]) whose mRNA transcript levels in plasma exosomes significantly increased among AMR compared with CMR and/or control patients. A gene combination score calculated from 4 genes of gp130, SH2D1B, TNFα, and CCL4 was significantly higher in the AMR than the CMR ( P < 0.0001) and no rejection control groups ( P < 0.01 vs DES control, P < 0.05 vs non-DES control). Conclusions: Our results suggest that plasma exosomes may contain information indicating clinical conditions of kidney transplant patients. mRNA transcript profiles based on gp130, SH2D1B, TNFα, and CCL4 in plasma exosomes may be used to predict on-going and/or imminent AMR. Abstract : In 152 kidney transplant recipients with or without antibody-mediated rejection (AMR), the authors study mRNA transcripts for 21 candidate genes in plasma exosomes and find a significant increase in patients with AMR. A score involving 4 specific genes may help AMR occurrence prediction. Supplemental digital content is available in the text.